2023
DOI: 10.3390/cryst13030440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dopants on Laser-Induced Damage Threshold of ZnGeP2

Abstract: The effect of doping Mg, Se, and Ca by diffusion into ZnGeP2 on the optical damage threshold at a wavelength of 2.1 μm has been studied. It has been shown that diffusion-doping with Mg and Se leads to an increase in the laser-induced damage threshold (LIDT) of a single crystal (monocrystal), ZnGeP2; upon annealing at a temperature of 750 °C, the damage threshold of samples doped with Mg and Se increases by 31% and 21% from 2.2 ± 0.1 J/cm2 to 2.9 ± 0.1 and 2.7 ± 0.1 J/cm2, respectively. When ZnGeP2 is doped wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…However, the prolonged operation of powerful OPOs and OPGs/OPAs based on ZGP is limited by the laser-induced damage (LID) of this material. In accordance with the results of numerous studies [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], the ZGP LID always occurs at the sample surface or in the sub-surface layer rather than in the bulk in samples subjected to repetitively pulsed nanosecond-pulse-width infrared radiation. A combination of factors associated with defects in the crystal structure in the sub-surface layer and the quality of polishing of the surface itself affects the LID.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, the prolonged operation of powerful OPOs and OPGs/OPAs based on ZGP is limited by the laser-induced damage (LID) of this material. In accordance with the results of numerous studies [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], the ZGP LID always occurs at the sample surface or in the sub-surface layer rather than in the bulk in samples subjected to repetitively pulsed nanosecond-pulse-width infrared radiation. A combination of factors associated with defects in the crystal structure in the sub-surface layer and the quality of polishing of the surface itself affects the LID.…”
Section: Introductionsupporting
confidence: 86%
“…There have been a number of publications on the problem of the ZGP LID induced by lasers operating at wavelengths from 1.064 µm to 10 µm [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. These studies have revealed a significant difference in the LIDT of ZGP crystals at wavelengths of 1.064 µm and 2.1 µm [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technologies for growing and processing these crystals are highly advanced. However, ongoing research efforts focus on improving the optical characteristics of these crystals through the incorporation of dopants during growth or through specific post-growth treatments [35][36][37]. Among these nonlinear materials, only the AGS crystal is suitable for the frequency down-conversion of the commonly used 1 µm solid-state laser to the mid-IR range.…”
Section: Introductionmentioning
confidence: 99%
“…The change in the LIDT threshold of a ZnGeP2 single crystal was achieved by diffusion doping of Mg, Se, and Ca into the single crystal, with Mg and Se leading to an increase in LIDT, and Ca, to a decrease in LIDT. [14] The goal of this paper is to verify the possibility of creating a sputtering detection system for ZnGeP2 crystals based on Raman spectroscopy combined with PCA-SVM analysis.…”
Section: Introductionmentioning
confidence: 99%